1995
DOI: 10.1111/j.1600-0684.1995.tb00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the natural immune response of rhesus monkey CD4+ve T cells to the bacterial antigen streptolysin O (SLO)

Abstract: Rhesus monkeys show a high proliferative T cell response to the bacterial exotoxin SLO without prior immunization. The present study was undertaken to characterize this naturally present SLO-responsiveness with particular emphasis on CD4+ve reactive T cells. It is demonstrated that the frequency of SLO-reactive cells in the circulation.ranges between 1 in 75 and 1 in 610 CD4+ve T cells as determined with limiting dilution analysis. It is also shown that induction of a good proliferative response requires Mhc-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…4). This result indicated that the long-term survivors, who were housed with the regular colony, were immunocompetent with respect to a common environmental microbial antigen (25). In this context, the absence of demonstrable anti-donor IgG to the abiding alloantigenic islets was seemingly specific.…”
Section: Resultsmentioning
confidence: 74%
“…4). This result indicated that the long-term survivors, who were housed with the regular colony, were immunocompetent with respect to a common environmental microbial antigen (25). In this context, the absence of demonstrable anti-donor IgG to the abiding alloantigenic islets was seemingly specific.…”
Section: Resultsmentioning
confidence: 74%
“…Pneumonia caused by the commensal fungus P. jiroveci is a well-recognized [52] complication in CD40L deficiency with incidence rates ranging from 32% to 42% [11,13]. However, reports of other fungal infections are rare: Candida in two patients [12,20], Cryptococcus in one patient [21], and Histoplasma in one patient [10]. While candidiasis and P. jiroveci infections usually occur during the first 5 years of life, the patients developing cryptococcosis and histoplasmosis and the Brazilian patient developing P. brasiliensis where 12, 19, and 11 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular mechanisms by which ML‐05 can facilitate wound healing also require further investigation. As a potential immunomodulator, ML‐05 could be affecting cytokine/chemokine expression, neutrophil and epithelial cell migration/proliferation, and other specific responses relevant to wound healing 10,13,14,19,20 . A variety of cytokines and chemokines are known to have a role in promoting keratinocyte migration, proliferation, and reepithelialization during wound healing 37,48–51 .…”
Section: Discussionmentioning
confidence: 99%
“…SLO and related substances can induce the production of a variety of cytokines and chemokines. [12][13][14][15][16] As an example of the favorable effects of cytokines on wound-healing processes, interferon-g and interleukin-12 (IL-12) have been shown to decrease abnormal collagen production associated with fibrogenesis in wound healing. 10,[17][18][19][20] Second, SLO and related compounds may increase or maintain the expression of cell surface receptors that are involved in ECM organization, notably hyaluronan receptor CD44.…”
mentioning
confidence: 99%